SPATIAL DISTRIBUTION OF CHLOROPHYLL-a IN CIRATA LAKE USING REMOTE SENSING - Syahras Fathin Aminuddin; Sunardi Sunardi; Prihadi Santoso (BIOTIKA Jurnal Ilmiah Biologi, 2015)
The research of spatial distribution chlorophyll-a in Cirata lake using remote sensing. The method used is secondary data collection, remote sensing, and statistical analysis. Remote sensing methodcomprising, Pansharpening, radiometric correction, interpretation and image extraction, and datapresentation. Statistical analysis performed correlation and linear regression to get the mappingformula chlorophyll-a. Purpose of this study is to apply remote sensing method as a tool monitoringof the Cirata lake. The research objective is to obtain a model of remote sensing data with the dataof chlorophyll-a.The results showed linear regression equation in the first quarter, Y= 13.982*(x)50.673with r = -0.33, R2=-0.007, and P-value=0.39.Secondquater,Y=4.366*(x)+2.442,r =0.33, R2 = -0.031, and P-value = 0.40. Third quater, Y= 7.394*(x)+9.393, r = 0.11, R2 = 0.29, andP-value = 0.79. Fourth quater, Y = 2.917*(x) + 8.324, r = 0.74, R2 = 0.70, and P-value = 0.022.Spatial distribution of chlorophyll-a in Cirata lake concentrated on central of the lake area markeddarker colors or chlorophyll-a concentration ≥ 10 mg/m3 with a clumped pattern. Intake area hasclumped pattern dominated the light colors or chlorophyll-a concentration ≥ 10 mg/m3 and inletarea has clumped pattern with a light color or chlorophyll-a concentration ≥ 8 mg/m3.